PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) PADA SISTEM HIDROPONIK NFT DENGAN BERBAGAI KONSENTRASI PUPUK AB MIX DAN GROWMORE - Riama RIta Manullang; Roby; F. Silvi Dwi Mentari; Rusmini (Politeknik Pertanian Negeri Samarinda, 2021)
One of the efforts to continuously increase lettuce production is by using hydroponic technology. Hydroponics is a way of farming without using soil media but using water or porous materials. Nutrient Film Technique (NFT) including hydroponic farming methods. In this system, some of the roots of the plants are submerged in water that contains fertilizer and some are above the surface of the water with a continuous 24 hours of circulation. The research was conducted from June to November 2020. The research was carried out on the Hydroponic Roof Top of the Red Building. Plantation Cultivation. This research method used a non-factorial randomized block design (RBD), the treatment of 1100 ppm AB Mix nutrition at the age of 1-14 days, 1300 ppm from the age of 21-28 days, 1500 ppm at the age of 29 - 35 days and B2 = Fertilizer Growmore 1100 ppm at the age of 1 - 14 and 1300 ppm from the age of 21 - 28 days, 1500 ppm at the age of 29 - 35 days Each treatment consists of 20 sample plants.The results showed a significant difference in the application of AB Mix fertilizer to Growmore fertilizer from week 1 to week IV on plant height increase, number of leaves and wet weight or yield on lettuce plants.